Isolation, identification and characterization of Burkholderia pseudomallei from soil of coastal region of India - Prakash, Archana (Springer International Publishing, 2014)
Melioidosis is an emerging infectious disease caused by a free living soil dwelling Gram-negative bacterium Burkholderia pseudomallei. The disease is endemic to most parts of Southeast Asia and northern Australia and the organism has been isolated from moist soil and water. In India clinical cases are recently reported from the states of Tamilnadu, Kerala, Karnataka, Maharashtra, Orissa, Assam, West Bengal, Pondicherry and Tripura. This study is aimed to confirm the prevalence of this important bacterial species in soil samples collected from coastal areas of Tamilnadu. Forty five soil samples from five different sites were collected from Parangipettai, Tamilnadu and screened for the presence of B. pseudomallei. The study confirmed 4 isolates as B. pseudomallei with the help of conventional bacteriological methods and molecular methods that include; 16S rDNA sequencing, B. pseudomallei specific PCR, fliC gene RFLP and MALDI-TOF mass spectrometry based bacterial identification. This study reveals the prevalence and distribution of B. pseudomallei in the soil environment in coastal areas of southern India and further necessitates studies from other parts of the country. It will also be helpful to understand the distribution of B. pseudomallei and to access its epidemiological importance.